2010
DOI: 10.4088/jcp.08m04722ora
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Symptoms in Adult Attention-Deficit/Hyperactivity Disorder

Abstract: Our findings illustrate the close relationship between some symptoms of BSD and ADHD in adults. In clinical and research settings, patients screening positive for BSD should be assessed for a possible underlying or coexisting ADHD condition and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 58 publications
1
36
0
Order By: Relevance
“…More recent studies have been critical to this diagnostic specificity [46], and have even shown an overlap between MDQ and ADHD reported symptoms [40,47]. We therefore decided to use the more global term of affective fluctuations to describe the functionally impairing symptoms assessed by the MDQ, and strict criteria to define affective fluctuation in order to distinguish MDQ symptoms from ADHD symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have been critical to this diagnostic specificity [46], and have even shown an overlap between MDQ and ADHD reported symptoms [40,47]. We therefore decided to use the more global term of affective fluctuations to describe the functionally impairing symptoms assessed by the MDQ, and strict criteria to define affective fluctuation in order to distinguish MDQ symptoms from ADHD symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…This may be explained by the heightened arousal characterizing individuals with affective disorders [38], and that this arousal contributes to cognitive impairment through its effect on EF [39]. Due to the high frequency of affective symptoms in adults with ADHD [40], these results motivate further studies using the ANT to investigate characteristics of alerting and control networks.…”
Section: Introductionmentioning
confidence: 99%
“…Other important comorbid conditions include anxiety (Edel et al 2009;Dineen andGallagher 2009), bipolar disorders (Bernardi et al 2009;Halmoy et al 2009) oppositional defiant and conduct disorder (Alvaani and Dalvand 2009;Franc et al 2009) and substance use (Feuz and Tschacher 2009).…”
Section: Differential Diagnosis and Comorbiditymentioning
confidence: 98%
“…All studies were carried out in accordance with the tenets of the Declaration of Helsinki and were approved by the respective local Norwegian, German, Danish and British local research ethical committees; see [30], [31], [32], [33], [34], [35], [36]. Written informed consent was given by all participants and in case of minors by their parents.…”
Section: Methodsmentioning
confidence: 99%
“…A sample of 466 Norwegian cases and 515 controls [31] was genotyped for markers covering the DCLK1 gene. For this sample we chose to genotype the markers (n = 20) that had been selected for the replication study in the BP sample.…”
Section: Methodsmentioning
confidence: 99%